Synthesis of C7/C8-cyclitols and C7N-aminocyclitols from maltose and X-ray crystal structure of Streptomyces coelicolor GlgEI V279S in a complex with an amylostatin GXG–like derivative - Thanvi, Radhika; Jayasinghe, Thilina D.; Kapil, Sunayana; Obadawo, Babatunde Samuel; Ronning, Donald R.; Sucheck, Steven J. (Frontiers in Chemistry, 2022)
C7/C8-cyclitols and C7N-aminocyclitols find application in the pharmaceutical sector as -glucosidase inhibitors and in the agricultural sector as fungicides and insecticides. In this study, we identified C7/C8-cyclitols and C7N-aminocyclitols as potential inhibitors of Streptomyces coelicolor (Sco) GlgE1‐V279S based on the docking scores. The protein and the ligand (targets 11, 12 and 13) were prepared, the states were generated at pH 7.0 ±2.0 and the ligands were docked into the active sites of the receptor via Glide™. The synthetic route was similar to our previously reported route used to obtain 4‐⍺‐glucoside of valienamine (AGV), except the protecting group for target 12 was a p-bromobenzyl ester to preserve the alkene upon deprotection. While compounds 11-13 did not inhibit GlgE1-V279S at the concentrations evaluated, an X-ray crystal structure of the Sco GlgE1-V279S/13 complex was solved to a resolution of 2.73 Å. This structure allowed assessment differences and commonality with our previously inhibitors and was useful for identifying enzyme-compound interactions that may be important for future inhibitor development. The Asp 394 nucleophile formed a bidentate hydrogen-bond interaction with the exocyclic oxygen atoms (C(3)-OH and C(7)-OH) similar to the observed interactions with the Sco GlgE1-V279S in a complex with AGV (PDB:7MGY). Additionally, the data suggests replacing the cyclohexyl group with more isosteric and hydrogen-bond donating groups to would increase binding interactions in +1 binding site.